Injury pattern of road traffic accident patients admitted in Assam medical college and hospital, Dibrugarh, Assam - Das, Basanta B.; Gogoi, Gourangie (International Journal Of Community Medicine And Public Health, 2017)
Background: Worldwide 1.24 million people died and 50 million people were injured due to road traffic accidents in 2010. India tops the list of road traffic accident fatality. There is a rising trend in the road traffic accident fatalities in Assam from 2291 deaths in 2012 to 8872 in 2014. Without appropriate action, by 2030; road traffic injuries are predicted to be the fifth leading contributor to the global burden of disease and injury. Methods:A hospital based descriptive study was done for duration of one year. All the admitted road traffic accident cases were followed from OPD and Causality registers to the respective departments. After obtaining written consent, data were collected by conducting oral interview using a pre-designed and pre-tested schedule. Results: Fracture (71.79%) was found to be the most common internal injury and Abrasion (72.8%) the most common external injury. Injury to brain was found in 16.84% of the patients. Visceral injuries were found in 10.64% of the patients. Conclusions:Motor vehicle injuries are major cause of both external and internal injuries. There is importance of identifying typical patterns of injury associated with road traffic accidents. It may help in the logical management of the victims and capacity building of trauma centres according to regional needs.